Flying disc-wing : development of a spinning mechanism - Ng, Eugene Jia Qi (2019)
This paper attempts to explore the feasibility of using a flying disc-wing as an Unmanned Aerial Vehicle (UAV) by studying methods to maintain its spinning motion. A two-dimensional model of a disc-wing is built to explore the method of using propulsive forces as the main driving force. Besides using propulsive forces, an electric motor method is also studied for comparison against the propulsive method. Lastly, to further understand the concept of controlling the spinning motion, the underlying flight dynamic properties of gyroscopic precession has to be studied. This is done through a partnership with another student, Mr Tan Jun Kiat, whom focuses on the experimental portion of the project while the Computational Fluid Dynamics study is presented in this paper. A three-dimensional model of a disc-wing is built in an attempt to capture the gyroscopic precession using a quasi-steady case. This simulation will facilitate to deepen the understanding the gyroscopic precession of a flying disc-wing UAV.